An Award to Nurture the Leaders: APSI–Raja Sabapathy Leadership Award (Supported by Dr. Somes Guha) - Kadam, Dinesh (Indian Journal of Plastic Surgery, 2020)
Leadership for any professional society needs visionary leaders, who are adequately motivated to assume the role. The Association of Plastic Surgeons of India (APSI) has instituted APSI–Raja Sabapathy Leadership Award (supported by Dr. Somes Guha) in 2019 to identify and nurture members with the potential to take up the leadership for the association in the future. The author, a first recipient, reflects on this innovative step.
Keywords: leadership; plastic surgery society; Sushruta–Guha Lecture; Association of Plastic Surgeons of India